2022
DOI: 10.1071/sh22070
|View full text |Cite
|
Sign up to set email alerts
|

Under-utilisation of cardioprotective glucose-lowering medication in diabetics living with HIV

Abstract: Diabetes is an increasingly common co-morbidity in people living with HIV (PLWH). Given new evidence demonstrating cardiovascular benefits of sodium glucose transporter 2 inhibitors (SGLT2i) and glucagon-like peptide 1 receptor agonists (GLP1RA) in diabetic patients, we reviewed medical charts of 262 PLWH at Monash Health through a 1-year retrospective cohort study to determine the rates of their use. Prevalence of diabetes was 13.4% (35) and 60% ( 21) had microvascular and macrovascular complications. Only 4%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Our findings on underutilization of SGLT2 inhibitors among PWH with DM2 receiving care in a large US Health care System compliment similar trends from a smaller cohort of PWH in Australia. 10 Such findings may reflect "clinical inertia" 11 or provider reluctance to adopt or intensify treatment with new therapeutics. With respect to reluctance in SGLT2 inhibitor prescribing, a survey-based study revealed that nonendocrinologists frequently reported discomfort in administering "diabetes medications" for purposes other than glucose-lowering (eg, cardiorenal protection).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings on underutilization of SGLT2 inhibitors among PWH with DM2 receiving care in a large US Health care System compliment similar trends from a smaller cohort of PWH in Australia. 10 Such findings may reflect "clinical inertia" 11 or provider reluctance to adopt or intensify treatment with new therapeutics. With respect to reluctance in SGLT2 inhibitor prescribing, a survey-based study revealed that nonendocrinologists frequently reported discomfort in administering "diabetes medications" for purposes other than glucose-lowering (eg, cardiorenal protection).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the lack of financial reimbursement of these medications may hinder their wide-scale usage in many settings. Generally, evidence showed that GLP-1 agonists are still under-utilized in diabetic patients with HIV [24]. Here, we focus on the potential benefits of liraglutide and semaglutide in people with HIV, and various therapeutic considerations to be warranted.…”
Section: Introductionmentioning
confidence: 99%